Creating the Bag-of-Words with Spatial Context Information for Image Retrieval - Li, Zhen Wei; Zhuo, Li; Liu, Xin; Zhang, Jing (Applied Mechanics and Materials, 2014)
Recently bag-of-words (BoW) model as image feature has been widely used in content-based image retrieval. Most of existing approaches of creating BoW ignore the spatial context information. In order to better describe the image content, the BoW with spatial context information is created in this paper. Firstly, image’s regions of interest are detected and the focus of attention shift is produced through visual attention model. The color and SIFT features are extracted from the region of interest and BoW is created through cluster analysis method. Secondly, the spatial context information among objects in an image is generated by using the spatial coding method based on the focus of attention shift. Then the image is represented as the model of BoW with spatial context. Finally, the model of spatial context BoW is applied into image retrieval to evaluate the performance of the proposed method. Experimental results show the proposed method can effectively improve the accuracy of the image retrieval.